Monoclonal antibodies to the haemagglutinin HA1 subunit of the pandemic influenza A/H1N1 2009 virus and potential application to serodiagnosis - Samuel, Dhanraj; Warrener, Lenesha; Hoschler, Katja (Journal of medical virology, 2011)
In order to provide specific serological reagents for pandemic influenza A/H1N1 2009 virus, monoclonal antibodies (Mabs) to recombinant haemagglutinin component HA1 (rHA1) were generated after fusing spleen cells from a mouse immunized with rHA1 protein derived from influenza strain A/California/06/09 H1N1 with a mouse myeloma cell line. Five hybridoma clones secreting Mabs specific for the rHA1 protein derived from pandemic influenza A/H1N1 2009 and not for rHA1 from seasonal H1N1 influenza strains A/Brisbane/59/07 and A/Solomon Islands/03/06 were identified by EIA. Mabs 7H4, 9A4, and 9E12 were reactive in Western blots with full length rHA and/or rHA1 subunit derived from A/California/06/09 strain. Only Mab 1F5 inhibited haemagglutination of turkey red blood cells with recombinant NIBRG-121 virus derived from A/California/07/09, but did not react in Western blots. Immunostaining of MDCK cells infected with NIBRG-121 was localized to the membrane/cytoplasm for four of the reactive Mabs. The differing reactivity of the Mabs in Western blots, immunostaining, EIA, and haemagglutination inhibition assay suggest that at least four of the five Mabs recognize different epitopes on HA1 of the pandemic influenza A/H1N1 2009 virus. Ferret antisera to pandemic influenza A/H1N1 2009 (A/England/195/09 and A/California/07/09 strains) and sera from human subjects vaccinated with Influenza A (H1N1) 2009 Monovalent Vaccine (CELTURA®, Novartis Vaccines, Germany), inhibit binding of 1F5-HRP to biotinylated rHA1 derived from A/California/06/09 in a competitive EIA, suggesting that the epitope recognized by this Mab also evokes an antibody response in infected ferrets and vaccinated humans. J. Med. Virol. 83:559-567, 2011.